Forgone and delayed care in Germany– inequalities and perceived health risk of unmet need - Jens Klein; Daniel Lüdecke; Olaf von dem Knesebeck (International Journal for Equity in Health)
Abstract Background Subjective unmet need is an established indicator of unequal access to medical care and is often measured by delaying and forgoing medically necessary treatment. Research on delayed and forgone care among the general population in Germany including different reasons, social deprivation measures, and the perceived health risk of unmet need is sparse. This study aims to examine reasons, inequalities, and health-related consequences of unmet need in terms of delayed and forgone care. Methods A cross-sectional online survey was carried out based on a randomly drawn sample of the German adult population in December 2022 (N = 2,201). Respondents were asked whether medical treatments were delayed or forgone in the past 12 months due to different reasons (waiting time, travel distance, financial costs). If unmet need was indicated, the respondents were subsequently asked about their perception of related health risks. Associations with individual social (sex, age, migration history, education, income) and regional factors (social deprivation) as well as insurance status were examined using multilevel logistic regressions analyses. Results Among N = 1,955 respondents who indicated need for medical care, 30% reported at least one reason for forgone care (waiting time 23%, financial costs 11%, travel distance 9%). In terms of delayed care, highest rate was found for waiting time (34%). Multilevel analyses revealed significant associations of unmet need with female sex, younger age, lower education, lower income, and statutory health insurance. Associations varied depending on the reason for unmet need. Differences in regional social deprivation were particularly found for forgone care due to distance. Between half and nearly two-thirds of the participants reported worsening of symptoms in case of unmet need. Associations with social characteristics were inconsistent. Discussion Unmet need is a prevailing issue in Germany and associated with perceived worsening of health, various indicators of social inequality, and health insurance. Reducing waiting times (e.g. through the further development of appointment service centres) and private co-payments as well as ensuring health care provision in deprived areas can contribute to a decrease of barrier-related unmet need and health risks. However, more in-depth studies are required to account for the complex nature of health care access.